PENGARUH LINGKUNGAN KERJA, INSENTIF DAN REWARD TERHADAP MOTIVASI KERJA KARYAWAN PADA PT. TIARA INDAH ABADI - Ni Putu Ariska Aprillyanti; I Wayan Suarjana; Bagus Nyoman Kusuma Putra (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
The progress of a company cannot be separated from its Human Resources. To ensure the achievement of goal alignment, organizational leaders are required to provide incentives, rewards and pay attention to the work environment as a reciprocal relationship between the organization and human resources. This study aims to determine the effect of the work environment, incentives and rewards on employee motivation at PT. Eternal Beautiful Tiara. This research was conducted at PT. Tiara Indah Abadi (Bali Branch) which is located at Jalan Gunung Agung No. 125 West Denpasar using a population and a sample of 50 employees. The sampling technique used in this research is the saturated sampling method or the census method. Data was collected through interviews, observations and questionnaires. The data analysis technique used in this study is multiple linear regression analysis which is processed using SPSS version 23 software. Based on the results of the analysis, this study shows that the work environment has a positive and significant effect on employee motivation at PT. Tiara Indah Abadi. Incentives have a positive and significant effect on employee motivation at PT. Tiara Indah Abadi. Reward has a positive and significant effect on employee motivation at PT. Tiara Indah Abadi.